Management of postoperative pain in children following extractions of primary teeth under general anaesthesia: a comparison of paracetamol, Voltarol and no analgesia - AMANDA O’DONNELL, MARY HENDERSON, JANICE FEARNE & DAVID O’DONNELL (IAPD and Blackwell, 2007)
The aim of this study was to compare three different pain relief regimes and the respective levels of pain recorded by children undergoing extractions of primary teeth under general anaesthesia.